Women Farmers' Livelihood Patterns of Mountain Prismatic Community - Ashari Ismail (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2022)
This study investigates  the livelihood of women farmers, in the prismatic (transition) mountain community of Kaili Village, West Suli District, Luwu, South Sulawesi, Indonesia. The pattern of women's work in the community is not only working in the domestic sphere ---- but also working in the public sphere, as an additional and main breadwinner. The approach used in observing this community was a naturalistic qualitative approach. The results of the research showed that the work role of women farmers, in gender relations (husband – wife; male – female) is a vocation that has economic consequences. Women's income earners --- these prismatic mountain communities are agricultural laborers, planting/picking cloves, making brown sugar and various other vocations. With this pattern of making a living, making men who were previously taboo working in the domestic sphere, actually shows pride in having taken part in helping their wives/women in their households as child keeper, cooking, fetching firewood and various other domestic activities.